Stress caused by sleep deprival: liver morphometric analysis - Oliveira, Marília Capuço (2013)
Objective: To evaluate the effect of stress induced by sleep deprivation on nuclear and cellular features of rat liver. Methods: 16 adult male Wistar rats (200–260 g) in controlled light cycle received diet with customary salt quantity and free access to water and food. The animals were divided into two groups with 8 animals each (experimental group and control group). Animals stayed in the same box (two at a time) during seven days and after that period they were weighted e separated. The control group animal continued in the same box and the experimental group animal were transferred to a sleep deprivation apparatus. After the 96 hours the animals were sacrificed by an excessive anesthetic dose; animals were weighted and their liver extracted. Results: There was no significant difference between experimental and control group regarding weight, although there was a decrease of weight on the experiment group. Karyotipical analysis showed significant smaller diameter (p=0.03) and volume (p=0.044) of hepatocyte nuclei in experimental group. Stereological analyses showed significant differences in experimental group for nucleus (larger, p=0.036), cytoplasm (smaller, p=0.009) and other structures (larger, p=0.008). Conclusion: Stress seems to contribute to alteration of hepatic cell structure.